Effect of glutaraldehyde biocide on laboratory-scale rotating biological contactors and biocide efficacy - Laopaiboon, Lakkana; Phukoetphim, Niphaphat; Laopaiboon, Pattana (Electronic Journal of Biotechnology, 2006)
The effect of glutaraldehyde, a commercial biocide widely used in paper and pulp industry, on the performance of laboratory-scale rotating biological contactors (RBCs) as well as biocide efficacy was studied. Biofilms were established on the RBCs and then exposed to 0 - 180 ppm glutaraldehyde at a dilution rate of 1.60 h-1. The results showed that the biofilms became acclimated to glutaraldehyde and eventually could degrade it. Acclimation to the biocide took longer at the higher biocide concentrations. The degree of biocide degradation and chemical oxygen demand (COD) removal depended on acclimation period, the presence of other organic matters and the amount of mineral salts available. Glutaraldehyde at up to 80 ppm had no effect on treatment efficiency and populations of biofilms and planktonic phase of the system whereas glutaraldehyde at 180 ppm caused a progressive decline in all measured values. However, no glutaraldehyde concentration used in the study was sufficiently high to kill microorganisms in the RBC system. The presence of biofilm provided additional resistance to glutaraldehyde to bacteria because the biocide had to penetrate through biofilm to reach bacteria. The increased resistance of bacteria to glutaraldehyde due to acclimation should be considered in biocide applications.